2021
DOI: 10.3390/s21206914
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Scale Effects of the Relationship between Fractional Vegetation Coverage and Land Surface Temperature in Horqin Sandy Land, North China

Abstract: Sandy range land refers to a major component of grassland area types in the semi-arid area of northern China. Monitoring of vegetation and land surface temperature (LST) using remote sensing technology can help determine the degree of desertification in a regional and/or sub regional scale, as in the Horqin Sandy Land selected in this study. Correlation analysis was performed to examine the relationship between the fractional vegetation coverage (FVC) and the LST within one growing season (from May to August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…Importance values indicated that urban and built-up lands and barren land area with low ecological quality in 2000 shown to have a greater impact on MRSEI, while water body and wetland with higher ecological quality in 2020 had a greater impact on MRSEI, this result is basically consistent with that of RSEI change research in Dongting Lake and can be mutually verified (Yuan et al, 2021). However, a common defect of RSEI and MRSEI is that the participating evaluation factors LDI, NDVI, and NDBSI reflect the long-term accumulated surface reflection characteristics, while Wet and LST only reflect the short-term surface reflection characteristics (Bindlish and Barros, 2001;Sobrino et al, 2008;Qiao et al, 2021). The removal of this uncertainty due to time scale mismatch is a challenge for RSEI and MRSEI applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importance values indicated that urban and built-up lands and barren land area with low ecological quality in 2000 shown to have a greater impact on MRSEI, while water body and wetland with higher ecological quality in 2020 had a greater impact on MRSEI, this result is basically consistent with that of RSEI change research in Dongting Lake and can be mutually verified (Yuan et al, 2021). However, a common defect of RSEI and MRSEI is that the participating evaluation factors LDI, NDVI, and NDBSI reflect the long-term accumulated surface reflection characteristics, while Wet and LST only reflect the short-term surface reflection characteristics (Bindlish and Barros, 2001;Sobrino et al, 2008;Qiao et al, 2021). The removal of this uncertainty due to time scale mismatch is a challenge for RSEI and MRSEI applications.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in the pattern analysis of land surface temperature (LST), it was found that the heat island effect in Leipzig (Germany), was more reliable in densely urbanized areas than in areas with low population density (Schwarz et al, 2012). The sandy vegetation pattern in Horqin (China) was negatively correlated with land surface temperature, and the more complex the vegetation structure, the closer the correlation (Qiao et al, 2021). These studies are of great significance for carrying out more targeted ecological restoration work, and are also the current hotspots for quantitatively describing and estimating the spatiotemporal dynamics of eco-environmental quality and promoting sustainable development in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the yield of this reaction, a screening of different ligands (TDG1−TDG5) was then carried out (Table 1, entries 1−5). It was found that the reaction with tert-leucine (TDG4) as the directing group gave a better yield (Table 1, entry 4); further screening of the solvents (Table 1, entries 6− 8) showed that the mixed solvent system HFIP/AcOH (9/1) proved to be more effective leading to a 42% yield of 3a (Table 1, entry 7). Next, the yield was increased to 49% by increasing the amount of transient directing ligand (TDG4) to 40 mol % (Table 1, entry 9).…”
Section: T H Imentioning
confidence: 99%
“…2 The remarkable progress has been applied in C(sp 2 )−H functionalization of aromatic aldehydes and ketones by employing monodentate or bidentate transient directing groups, such as arylation, 3 halogenation, 3d,4 hydroxylation, 5 methoxylation, 4b alkylation, 4a,6 amidation, 7 and selenylation. 8 Meanwhile, more challenging C(sp 3 )−H bond functionalizations of aliphatic aldehydes and ketones with various transient ligands have been significantly developed by the groups of Yu, 9 Ge, 10 Bull, 11 Wei, 12 Zhou, 13 Zhang, 14 and Li. 15 Unsurprisingly, the benzylic C(sp 3 )−H functionalization of 2-alkylbenzaldehyde, a critical building block, 16 has been accomplished with this novel synthetic strategy.…”
mentioning
confidence: 99%
“…Many scholars at home and abroad have done a lot of research in the field of public transportation. Evaluated the * Corresponding author accessibility and fairness of public transport and car transport from the perspective of time cost of traffic travel (Xi ,2020).Evaluated the scale effect and spatial effect affecting the spatial fairness mechanism of public transport (Li ,2019) .Studied the influence of spatial scale changes on bus fairness evaluation (Qiao, 2021), bus system optimization (Bai, 2017) and (Ge, 2006) and (Wirasinghe, 1981) and (Li, Bertini, 2009), and public transport accessibility (Ribeiro, 2021) and (Gao, Zhang,2022) and (Liu, Wang, 2011). Public transport passenger flow analysis (Gutié rrez et al, 2020) and (Liang, 2007), multi-use space autocorrelation analysis (Zhang et al, 2012), Gini coefficient (Liu et al, 2021), kernel density analysis (Yu, Ai, 2012) and other research methods in relevant literature.…”
Section: Introductionmentioning
confidence: 99%